Peningkatan Literasi Braille pada Anak Tunanetra - Rafael Lisinus Ginting; Anggita Farahdiba; Dito Harisandy; Elviani Van Gracella Sinaga; Frisca Monalisa Purba; Fikri Raspati; Helmi Reza Musyafa; Muhammad Habib Putra (Universitas Palangka Raya, 2024)
This research explores Efforts to increase Braille literacy and daily living skills in blind children through an inclusive education approach. By collaborating with special education institutions, we design innovative learning methods to strengthen Braille literacy understanding and increase the independence of blind children in daily activities. The research results show that this approach has succeeded in having a positive impact on the holistic development of blind children, enabling them to be more active and independent in society.